Infection-Related Glomerular Nephritis: Understanding the Kidney’s Immune Battle - Salimath, Geetanjali Shankar Prasad; Dias, Angelica Carina Maria (Indian Journal of Pharmacy Practice)
Infection-Related Glomerulonephritis (IRGN) is a type of glomerulonephritis, which is a group of diseases that damage the kidneys' filtering units called glomeruli. IRGN specifically occurs as a result of an infection in the body, often caused by bacteria like streptococcus or staphylococcus. These bacteria release toxins that can trigger an immune response against the bacterial infections in the glomeruli, leading to inflammation and kidney damage. Common infections associated with IRGN include throat or skin infections, such as strep throat or impetigo. The immune response causes the glomeruli to become inflamed, impairing their ability to filter waste and excess fluids from the blood properly. As a result, the kidneys may not function efficiently, leading to symptoms like hematuria (blood in the urine), proteinuria (excess protein in the urine), high blood pressure and swelling in the face, hands, legs, or feet. Diagnosis of IRGN involves a physical examination, blood tests, urine tests and sometimes a kidney biopsy to confirm the presence of glomerular inflammation. Treatment typically focuses on managing the underlying infection with antibiotics and addressing the symptoms. In severe cases, especially if kidney function is significantly impaired, additional therapies such as immunosuppressive medications or dialysis might be necessary. It's essential for individuals with symptoms suggestive of kidney problems, especially if they have a recent history of infections, to seek medical attention promptly. Early diagnosis and appropriate management can help prevent complications and preserve kidney function.
Keywords: Glomerulonephritis; Bacterial infections; Immune response; Kidney function; Diagnosis